Detection and reporting of RB1 promoter hypermethylation in diagnostic screening. (4th July 2018) - Price, Elizabeth A.; Kolkiewicz, Kelly; Patel, Roopal; Hashim, Sugera; Karaa, Esin; Scheimberg, Irene; Sagoo, Mandeep S.; Reddy, M. Ashwin; Onadim, Zerrin
ABSTRACT: Background: RB1 gene screening aids clinical management and genetic counselling in retinoblastoma families. Here we present epigenetic changes identified during routine molecular RB1 screening of tumor and blood samples. Complications in interpreting RB1 methylation are discussed. Materials and Methods: Screening for RB1 promoter hypermethylation was carried out by Methylation Specific PCR (MS-PCR) after bisulphite modification of DNA. The cohort consisted of 315 tumors, and 204 blood samples, from 497 retinoblastoma patients (22 patients had both blood and tumor screened). Results: 11.4% of retinoblastoma tumors had promoter hypermethylation. It was not routinely detected in blood samples, or in tumors with two other oncogenic RB1 changes. One blood sample had promoter hypermethylation due to an X;13 translocation. One tumor had low level methylation as well as two other oncogenic changes. Histopathological analysis of a small subset of age-matched tumors was similar regardless of promoter hypermethylation status. Conclusions: Promoter hypermethylation was detected in 11.4% of the retinoblastoma tumors and should be tested for in routine RB1 screening programmes. Constitutional samples are not expected to display RB1 hypermethylation. In a small proportion of cases it may not be possible to use this somatic change in patient management.